The art of plant-based cheesemaking : how to craft real, cultured, non-dairy cheese - McAthy, Karen (Urban homesteader hacks., 2017)
"Packed with simple methods, clear recipes, and straightforward guidelines, The Art of Plant-Based Cheesemaking arms the reader with a clear understanding of the processes for creating authentic cultured, non-dairy, plant-based cheese using traditional (dairy) cheesemaking methods. It gives permission and calls on the reader to experiment, adapt, and have fun with easy and advanced plant-based cheese recipes."--